Gastric perforation by a trichobezoar â Case report - Mafalda Sousa-Cardoso; Ana Catarina-Rosa; Tiago Ferro; Joana Pereira; Rui Alves; Isabel Brito-Lança (Publicaciones Permanyer, 2024)
Introduction: Bezoars are masses resulting from the ingestion and accumulation of undigested material in the gastrointestinal tract. They can be divided into trichobezoars (hair), phytobezoars (plant fibers), pharmacobezoars (drugs), and lactobezoars (cow's milk). The most common symptoms are abdominal pain, nausea, vomiting, anorexia, and weight loss. Case report: We report the clinical case of a 13-year-old boy with a trichobezoar that had developed over the course of several years, which resulted in gastric perforation. A surgical laparotomy was performed to remove the trichobezoar and close the gastric wall. Discussion: Trichobezoars can present in the form of an acute abdomen. In these situations, surgical treatment is necessary.